Penatalaksanaan Fisioterapi pada Kasus Ischialgia Bilateral Et Causa Spondylolisthesis di RSUD Salatiga - Mu'awanah, Ridwanah, Edy Waspada, S.Fis., M.Kes, Wahyuni, S. Fis, M.Kes, Dwi Rosella KS, S.Fis, M.Fis (2017)
PHYSIOTHERAPY MANAGEMENT IN THE CASE OF ISCHIALGIA BILATERAL ET CAUSA SPONDYLOLISTHESIS IN SALATIGA'S HOSPITAL (Ridwanah Mu'awanah, J100140037, 2017, 50 pages) ABSTRACT Background : Sciatica is a symptom of pain radiating along the Sciatic nerve distribution. Many factor that cause sciatica, which one of them is Spondylolisthesis. Purpose : To study physiotherapy management in the case of Ischilgia Bilateral et causa Spondylolisthesis with modalities Microwave Diathermy and William Flexion Exercise. Result : Silent pain T1 : 2 cm , T6 : 1 cm, tenderness T1 : 4 cm, T6 : 2 cm, pain motion T1 : 7 cm, T6 : 3 cm. Increased muscle strength flexor trunk T1 : 3, T6 : 4, extensor trunk T1 : 2, T6 : 3, flexor hip dextra T1 : 4, T6 : 5, extensor hip dextra T1 : 4, T6 : 5, abductor hip dextra T1 : 4, T6 : 5, adductor hip dextra T1 : 4, T6 : 5, endorotator hip dextra T1 : 4, T6 : 5, exorotator hip dextra T1 : 4, T6 : 5, flexor hip sinistra T1 : 4, T6 : 5, extensor hip sinistra T1 : 4, T6 : 5, abductor hip sinistra T1 : 4, T6 : 5, adductor hip sinistra T1 : 4, T6 : 5, endorotator hip sinistra T1 : 4, T6 : 5, exorotator hip sinistra T1 : 4,T6 : 5. Increase flexibility flexi trunk T1 : 8 cm, T6 : 10 cm, extensi trunk T1 : 2 cm, T6 : 3 cm, side flexi dextra T1 : 9 cm, T6 : 9 cm, side flexi sinistra T1 : 11 cm, T6 : 11 cm. Improved functional abilities at T1 : 42 %, T6 : 34 %. Conclusion : Microwave Diathermy (MWD) and William Flexion Exercise can reduce pain in the case Ischialgia. Keyword : Ischialgia , Spondylolisthesis, Microwave Diathermy (MWD), William Flexion Exercise.